(3MGTjI Ydi Ce GdHQGgjf ddSfhSjs - (3eLghds
(3ChdgG (B:s
(3HSe Gddg bGd GdTjN CHh YHO Gddg SjOj eMeO Hf jhSa GdSfhSj GdMSfj GYde Cf GdMce GdYbdj efMUQ aj KdGKI CbSGe GdhLhH hGdGSJMGdI hGdLhGR; aGdhGLH s
(3BNQgG (B:s
(3Ydjg ef YbGFO GdEjeGf MJi JeJRL eY eYfGgG HdMeg hOeg aEfg jQi dgG ef GdCSQGQ hGdYLGFH Ef TGA Gddg JYGdi eGG jONd JMJ MUQ hHGddg JYGdi GdJhajb JeJs
(3eUOQ GbJfGA GdCUd (B:s
(3Ydj CejQjs
(3ehGUaGJ GdhYGA (B:s
(3Qbej edhfs
(3ehGUaGJ GdfSNI (B: s
(3MGdI GdfSNI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds